A Graph Theory Approach for Spatial Data-Based Surface Water Flow Modeling - Firgiawan, Wawan; Nirwana, Hafsah; Wajidi, Farid; Zainuddin, Zahir; Ahyar, Muh. (SINTECH (Science and Information Technology) Journal, 2024)
This research proposes an innovative approach that combines graph theory with spatial data to model surface water flow with the Single Flow Direction (SFD) concept, also known as the D8 algorithm. The objective is to show the water flow from the ground surface to a lower place. The research methodology involves collecting spatial data from the Digital Elevation Model (DEMNAS) in raster data type format. Test results show that the effectiveness of the graph approach in modeling water flow can produce clear flow output. This happens because each pixel traversed by water is connected by a line that forms a well-defined water flow path. This study significantly stimulates the development of more sophisticated modeling tools and practical applications in the future. This can help in more efficient management of water resources or produce more accurate flow modeling, contributing to improved understanding and better management of the environment.